Age, growth and fecundity of the silver mullet, Mugil curema (Pisces: Mugilidae), in coastal arcas of Northeastern Venezuela - Marin E, Baumar J (Universidad de Costa Rica, 2000)
We studied fecundity and growth in populations of the silver mullet, Mugilcurema, in coastal areas of northeastern Venezuela between March 1992 and July 1993. The average number of oocytes in gonads of 23-42 cm adults was 54 x 104, and lhe relative fecundity was ! 311 oocytes g-I of fish. The size of mature oocytes did not vary in different portions of the same gonad (p > 0.05) or among the adults in three populations studied. The average egg diameter for adults was 426 ¡lm (CI=4.34). Age of juveniles, colIected from the La Restinga Lagoon at about monthly intervals, from counts of growth lines on the otoliths ranged from 50 to 240 days. The relation of age (number of growth lines) to standard length follows an exponential growth curve. The growth ofjuveniles varied seasonally and was greatest during the rain y season C April to August), when temperatures were highes!. The time of spawning has probably been adapted so Ihat peak recruitment into the lagoons occurs just prior lo the rainy season when conditions for growth are most favorable.